Study of Geodetic datum of Nepal, China and Pakistan and its transformation to World Geodetic System - Manandhar, Niraj (Journal on Geoinformatics, Nepal, 2011)
There are many government, non-government and International organizations dealing in compilation of database or electronic maps with data from different sources often becomes necessary to transform from one coordinate system to another in order to work within a single unifying framework. The significance of the study of the coordinate system of China, Pakistan, Nepal will benefit many researchers working in various disciplines and using geographic information system a part of their research. The use of remotely sensed data for environmental studies, disaster related matters and many more has widely been in use due to the availability of high resolution satellite images but it requires to have a relationship between the satellite images and ground location called geo-referencing. To establish this relationship the understating of the coordinate system is needed and also integrating to the national grid of the particular country if required then further knowledge of the parameters of datum chosen by the particular country will be a must. This paper illustrates some findings of the coordinate system of this region.